Trade Liberalization and Shadow Prices in the Presence of Tariffs and Quotas. - Neary, J (CEPR, 1989)
This paper examines the welfare effects of partial trade liberalization when trade is restricted by tariffs, quotas or some combination of both instruments. Rules for optimal first- and second-best intervention are derived and illustrated (using a new geometric technique) in both small and large open economies. A general expression for shadow prices of factors of production, which applies in both small and large economies, with or without quotas, is also derived. Welfare paradoxes are possible whenever exogenous changes raise (lower) imports of goods subject to trade restrictions which are below (above) optimal levels.